2013
DOI: 10.1016/j.cbd.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oils mediate cortisol kinetics and the hepatic mRNA expression profile of stress-responsive genes in gilthead sea bream (Sparus aurata) exposed to crowding stress. Implications on energy homeostasis and stress susceptibility

Abstract: Running title: Nutritional background and stress challenges AbstractJuveniles of gilthead sea bream were fed with plant protein-based diets with fish oil (FO diet) or vegetable oils (66VO diet) as dietary lipid sources. No differences in growth performance were found between both groups, and fish with an average body mass of 65-70 g were crowded (90-100 kg/m 3 ) to assess the stress response within the 72 h after the onset of stressor. The rise in plasma cortisol and glucose levels was higher in stressed fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 59 publications
(52 reference statements)
4
37
0
1
Order By: Relevance
“…As reported by Perez-Sanchez et al (2013), crowding causes a complex stress by affecting hepatic gene expression, antioxidant defence system, cell-tissue repair mechanism, xenobiotic metabolism and stress transcriptional regulation. This response, similar to the one described by Bayir et al (2014) for starvation, may explain the funding of Bagni et al (2007), that monitored the effect of crowding (density >70 kg/m 3 ) on the oxidative stress of two common Mediterranean species (gilthead sea bream, S. aurata, and European sea bass, Dicentrarchus labrax).…”
Section: Pre-slaughter Procedure: Starvation and Crowdingmentioning
confidence: 94%
“…As reported by Perez-Sanchez et al (2013), crowding causes a complex stress by affecting hepatic gene expression, antioxidant defence system, cell-tissue repair mechanism, xenobiotic metabolism and stress transcriptional regulation. This response, similar to the one described by Bayir et al (2014) for starvation, may explain the funding of Bagni et al (2007), that monitored the effect of crowding (density >70 kg/m 3 ) on the oxidative stress of two common Mediterranean species (gilthead sea bream, S. aurata, and European sea bass, Dicentrarchus labrax).…”
Section: Pre-slaughter Procedure: Starvation and Crowdingmentioning
confidence: 94%
“…For the remaining sampled points, the analysed gene panel was identical. The primer sequences of GK, G6Pase, COX4, CS and elongation factor 1 (EF1) genes used for real-time qPCR have previously been published for this species (Bermejo-Nogales et al, 2014;Enes et al, 2008a;Perez-Sanchez et al, 2013). For the other analysed genes, specific primers were designed for gilthead seabream using the Primer3 software (http://primer3.ut.ee/) and the available seabream sequences from the nucleotide GenBank (http://www.ncbi.nlm.nih.…”
Section: Gene Expression Analysis By Qrt-pcrmentioning
confidence: 99%
“…In addition, Remen et al (2015) has shown in sea bream that the limiting O 2 saturation value (LOS, also termed as Pcrit) is approximately 2.3 mg O 2  l −1 at 19°C, which is within the average range of Pcrit value reported by Rogers et al (2016) for other marine species. S. aurata increases hepatic antioxidant enzyme activities when subjected to hypoxia (Pérez-Jiménez et al, 2012b), and modulates the hepatic expression of several genes involved in β-oxidation, oxidative stress response, and energy generation in mitochondria in response to different dietary lipid sources (Pérez-Sánchez et al, 2013; Saera-Vila et al, 2009). Also, the oxidative status of sea bream is improved upon dietary supplementation with essential amino acids when fed plant protein-based diets (Sitjà-Bobadilla et al, 2005) or when antioxidants, such as methionine and white tea, are supplied in the diet (Pérez-Jiménez et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%